The role of explanatory models of chronic hepatitis B on illness experience: a qualitative study of Vietnamese participants in Australia. Issue 8 (17th November 2021) - Le Gautier, Roslyn; Wallace, Jack; A. Richmond, Jacqueline; Pitts, Marian
ABSTRACT : Objective: This study utilises Kleinman's theory of explanatory models of health and illness to explore the experience of chronic hepatitis B (CHB) among Vietnamese people living in Australia. It examines how these explanatory models are formed and shaped by the broader community, and the extent to which this influences understandings and responses to CHB. Design: This study is based on semi-structured interviews with 22 Vietnamese people with CHB in Melbourne, Australia. The individual interviews ranged from 30 minutes to 1.5 hours in length, and were electronically recorded, translated where necessary and transcribed verbatim. Transcripts were thematically coded using NVivo 10, with coding themes guided by categories identified in Kleinman's explanatory models framework. Results: Fundamental to most participants' narratives was the profound impact of cultural, social and economic environments on their understandings and responses to CHB. Regardless of socio-demographic background, most participants juxtaposed biomedical elements of CHB with their own existing humoral-based health belief system. In the context of a chronic asymptomatic condition that, for the most part, does not require pharmaceutical treatment, a humoral-based health belief system provided a familiar conceptual framework from which participants could immediately respond and take control of their infection. This was observed through changes in diet and lifestyle, and the use of traditional herbal medicine in an attempt to 'cure' or halt the progression of their infection. Conclusions: By speaking to people living with CHB directly, it became clear that there is a disjuncture between what is commonly assumed by the biomedical model of CHB and what is understood by individuals with the infection. The public health burden of CHB will continue unless the healthcare system, including public health policies, deliver a hepatitis B model of care that is responsive to the needs and expectations of priority populations.